Efektivitas Pemberian Serbuk Jambu Biji Merah terhadap Peningkatan Kadar Hemoglobin pada Mencit (Mus musculus) - Septi Anggraeni; Eka Handayani; Bayu Rakhmat Muslimin (Jurnal Kesehatan Indonesia, 2021)
Anemia is a condition where hemoglobin and erythrocyte levels are lower than normal values. According to WHO, the prevalence of anemia is still considered to be a public health problem. The prevalence of anemia in Indonesia was 21,7%. Anemia prevention among adolescents is essential, and it can be done in two ways (i.e., pharmacology and non-pharmacology). Pharmacological methods included administration of Fe tablets, but not all teenagers wanted to consume these tablets for various reasons (e.g., bad taste and odor, side effects, forgot, and they felt that it was unnecessary). Therefore, this problem needed to be overcome by other methods (non-pharmacological methods), one of which was the use of red guava fruit. This study aimed to determine the effectiveness of red guava powder to increase hemoglobin levels. This experimental study used a posttest-only control group design. This study used 30 mice with an average weight of 20 g. The independent t-test results showed significant differences (p=0,001) in hemoglobin levels in the control group and the treatment group. It could be concluded that the provision of red guava powder was effective in increasing hemoglobin levels.